Role of transporters in plant disease resistance. Issue 4 (29th March 2021) - Devanna, Basavantraya N.; Jaswal, Rajdeep; Singh, Pankaj Kumar; Kapoor, Ritu; Jain, Priyanka; Kumar, Gulshan; Sharma, Yogesh; Samantaray, Sanghamitra; Sharma, Tilak R.
Abstract: Plants being sessile have evolved numerous mechanisms to meet the changing environmental and growth conditions. Plant pathogens are responsible for devastating disease epidemics in many species. Transporter proteins are an integral part of plant growth and development, and several studies have documented their role in pathogen disease resistance. In this review, we analyze the studies on genome‐wide identifications of plant transporters like sugars will eventually be exported transporters (SWEET), multidrug and toxic compound extrusion (MATE) transporters, ATP‐binding cassette (ABC) transporters, natural resistance‐associated macrophage proteins (NRAMP), and sugar transport proteins (STPs), all having a significant role in plant disease resistance. The mechanism of action of these transporters, their solute specificity, and the potential application of recent molecular biology approaches deploying these transporters for the development of disease‐resistant plants are also discussed. The applications of genome editing tools, such as CRIPSR/Cas9, are also presented. Altogether the information included in this article gives a better understanding of the role of transporter proteins during plant‐pathogen interaction.